Liquidity provider incentives in fragmented securities markets - Benjamin Clapham; Peter Gomber; Jens Lausen; Sven Panz (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
We study the introduction of single-market liquidity provider incentives in fragmented securities markets. Specifically, we investigate whether fee rebates for liquidity providers enhance liquidity on the introducing market and thereby increase its competitiveness and market share. Further, we analyze whether single-market liquidity provider incentives increase overall market liquidity available for market participants. Therefore, we measure the specific liquidity contribution of individual markets to the aggregate liquidity in the fragmented market environment. While liquidity and market share of the venue introducing incentives increase, we find no significant effect for turnover and liquidity of the whole market.
urn:nbn:de:hebis:30:3-469256
Keywords: G10; G14; 330; Liquidity; Trading Volume; Market Fragmentation; Liquidity Provider Incentives; Transaction Costs